Realization of fractional-layer transition metal dichalcogenides - Ya-Xin Zhao; Heng Jin; Zi-Yi Han; Xinlei Zhao; Ya-Ning Ren; Ruo-Han Zhang; Xiao-Feng Zhou; Wenhui Duan; Bing Huang; Yu Zhang; Lin He (Nature Communications)
Abstract Layered van der Waals transition metal dichalcogenides (TMDCs), generally composed of three atomic X-M-X planes in each layer (M = transition metal, X = chalcogen), provide versatile platforms for exploring diverse quantum phenomena. In each MX2 layer, the M-X bonds are predominantly covalent in nature and, as a result, the cleavage of TMDC crystals normally occurs between the layers. Here we report the controllable realization of fractional-layer WTe2 via an in-situ scanning tunneling microscopy (STM) tip manipulation technique. By applying STM tip pulses, hundreds of the topmost Te atoms are removed to form a nanoscale monolayer Te pit in the 1 T′-WTe2, thus realizing a 2/3-layer WTe2 film. Such a configuration undergoes a spontaneous atomic reconstruction, yielding a unidirectional charge density redistribution with the wavevector and geometry quite distinct from that of pristine 1 T′-WTe2. Our results expand the conventional understanding of the TMDCs and are expected to stimulate further research on the structure and properties of fractional-layer TMDCs.